Hypoxia enhances H2O2-mediated upregulation of hepcidin: evidence for NOX4-mediated iron regulation - Silva, Ines; Rausch, Vanessa; Peccerella, Teresa; Millonig, Gunda; Seitz, Helmut K.; Mueller, Sebastian (Redox Biology, 2018)
The exact regulation of the liver-secreted peptide hepcidin, the key regulator of systemic iron homeostasis, is still poorly understood. It is potently induced by iron, inflammation, cytokines or H2O2 but conflicting results have been reported on hypoxia. In our current study, we first show that pronounced (1%) and mild (5%) hypoxia strongly induces hepcidin in human Huh7 hepatoma and primary liver cells predominantly at the transcriptional level via STAT3 using two hypoxia systems (hypoxia chamber and enzymatic hypoxia by the GOX/CAT system). SiRNA silencing of JAK1, STAT3 and NOX4 diminished the hypoxia-mediated effect while a role of HIF1α could be clearly ruled out by the response to hypoxia-mimetics and competition experiments with a plasmid harboring the oxygen-dependent degradation domain of HIF1α. Specifically, hypoxia drastically enhances the H2O2-mediated induction of hepcidin strongly pointing towards an oxidase as powerful upstream control of hepcidin. We finally provide evidences for an efficient regulation of hepcidin expression by NADPH-dependent oxidase 4 (NOX4) in liver cells. In summary, our data demonstrate that hypoxia strongly potentiates the peroxide-mediated induction of hepcidin via STAT3 signaling pathway. Moreover, oxidases such as NOX4 or artificially overexpressed urate oxidase (UOX) can induce hepcidin. It remains to be studied whether the peroxide-STAT3-hepcidin axis simply acts to continuously compensate for oxygen fluctuations or is directly involved in iron sensing per se.
Available online: 12 February 2018
Gesehen am 18.07.2018
Im Titel ist die Zahl 2 tiefgestellt